Environmental impact factors on Thai biomass power projects: A structural equation model - Aueatchasai, Somboon; Fongsuwan, Wanno (My University, 2015)
This study discusses factors, relating to the environmental impact of biomass power generation within Thailand and the broader regional ASEAN community. While there are ambitious government targets to increase the share of renewable energy in many countries, it is increasingly recognized that social acceptance may be a constraining factor in achieving this target. This study introduces three dimensions of environmental impact namely; public perception, government policy and community participation. Thailand's economic growth is in many respects determined by power generation with electricity demand moving hand-in-hand with rapidly expanding economic growth. With the doubling of Thailand's population since the 1960s, the necessity for rural electricity coverage has also increased dramatically. This, however, is at times difficult and expensive to achieve in these remote rural locations with their sparsely populated areas. However, power must be available nationwide and when areas are not appropriate for a large-scale power plant investment, smaller and less expensive local power plants are required. In these rural cases, biomass power plants can be considered as one alternative. Since, Thailand outside the main metropolitan areas is still mostly rural and agricultural, there is a ready source of raw material for biomass conversion. This study undertook the modeling and analysis of Thailand's biomass industry using both quantitative and qualitative research methods. Results showed from the hypotheses that public perception, government policy and community participation had a significant and direct contribution on the overall environmental impact of the local community.
Keywords: Biomass; Environment; Power plant; Thailand